Community Dialogues for Child Health: Results from a Qualitative Process Evaluation in Three Countries - Martin, Sandrine; Leitão, Jordana; Muhangi, Denis; Nuwa, Anthony; Magul, Dieterio; Counihan, Helen (Journal of Health, Population and Nutrition, 2017)
Across the developing world, countries are increasingly adopting the integrated community case management of childhood illnesses (iCCM) strategy in efforts to reduce child mortality. This intervention’s effectiveness is dependent on community adoption and changes in care-seeking practices. We assessed the implementation process of a theory-driven community dialogue (CD) intervention specifically designed to strengthen the support and uptake of the newly introduced iCCM services and related behaviours in three African countries.A qualitative process evaluation methodology was chosen and used secondary project data and primary data collected in two districts of each of the three countries, in purposefully sampled communities. The final data set included 67 focus group discussions and 57 key informant interviews, totalling 642 respondents, including caregivers, CD facilitators community leaders, and trainers. Thematic analysis of the data followed the ‘Framework Approach’ utilising both a deduction and induction process. Results show that CDs contribute to triggering community uptake of and support for iCCM services through filling health information gaps and building cooperation within communities. We found it to be an effective approach for addressing social norms around child care practices. This approach was embraced by communities for its flexibility and value in planning individual and collective change.Regular CDs can contribute to the formation of new habits, particularly in relation to seeking timely care in case of child sickness. This study also confirms the value of process evaluation to unwrap the mechanisms of community mobilisation approaches in context and provides key insights for improving the CD approach.
Keywords: Community engagement, Process evaluation, Behaviour change, Health communication, Dialogue, Zambia, Mozambique, Uganda